Magic involvement: The codification of possession in Middle Dutch healing recipes and charms - Letizia Vezzosi (Filologia Germanica)
It has long been debated whether recipes and charms represent separate textual genres. They have much in common in terms of structure, linguistic features and communicative purpose. The present paper approaches the issue from a linguistic perspective: it focusses on possessive constructions, and particularly on the question how body part nouns are syntactically incorporated in clauses. Empirically, this study is based on a corpus of Middle Dutch medical treatises and healing charm from the fifteenth century. It shows that charms and recipes presuppose a different communicative pact between the writer – i.e. the practitioner or the agician – and the patient. The resulting differences sufficiently substantial to warrant the conclusion that recipes and charms should be considered as different text types.